The memoir of lieutenant Dumont, 1715-1747 : a sojourner in the French Atlantic - Dumont de Montigny (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia., 2012)
In 1719, Jean-François-Benjamin Dumont de Montigny set sail for Louisiana with a commission as a lieutenant after a year in Quebec. His adventures over the next 18 years, as recorded in his 1747 memoir, underscore the complexity of the expanding French Atlantic world, offering a singular perspective on early colonialism in Louisiana. His life story also provides detailed descriptions and illustrations of the peoples and environment of the lower Mississippi valley. Dumont emerges here as an important colonial voice and brings the French vividly to life.